In silico design, synthesis and activity of potential drug-like chrysin scaffold-derived selective EGFR inhibitors as anticancer agents. (December 2019) - Debnath, Sudhan; Kanakaraju, Manupati; Islam, Minarul; Yeeravalli, Ragini; Sen, Debanjan; Das, Amitava
Graphical abstract: A series of C-7-hydroxyproton substituted chrysin derivatives were virtually drawn and were screened using 3D QSAR model created from forty-two known EGFR tyrosine kinase inhibitors. The best pharmacophore matched hits were then subjected to molecular docking followed by ADME filtration. The selected inhibitors were synthesized and subjected to a comparative in vitro investigation of the biological activity depicting a 3.2–fold enhanced cytotoxicity of chrysin derivative, CHM-04 against breast cancer cells as compared with chrysin. Highlights: In silico, ligand and structure-based drug designing approach led to the identification of new EGFR inhibitors. 3D QSAR–based virtual screening of a small library of C-7-hydroxyproton substituted chrysin derivatives. Based on predicted activity and XP glide score of molecular docking analysis, three EGFR inhibitors were synthesized. ADME analysis of the three selected inhibitors depicted drug-like properties. CHM-04 depicted potent pro-apoptotic activity, decrease migratory and in vitro tumorigenic potential of breast CSCs. Abstract: Background & objective: Epidermal growth factor receptor (EGFR) signaling pathway is one of the promising and well-established targets for anticancer therapy. The objective of the present study was to identify new EGFR inhibitors using ligand and structure-based drug designing methods, followed by a synthesis of selected inhibitors and evaluation of their activity. Methods: A series of C-7-hydroxyproton substituted chrysin derivatives were virtually drawn to generate a small compound library that was screened using 3D QSAR model created from forty-two known EGFR tyrosine kinase inhibitors. Next, the obtained hits with fitness score ≥ 1.0 were subjected to molecular docking analysis. Based on the predicted activity and XP glide score, three EGFR inhibitors were synthesized and characterized using 1 H-NMR, 13 C-NMR and MS. Finally, comparative in vitro investigation of the biological activity of synthesized inhibitors was performed with that of the parent molecule, chrysin. Results: The data depicted a 3.2–fold enhanced cytotoxicity of chrysin derivative, CHM-04 against breast cancer cells as compared with chrysin as well as its binding with EGFR protein. Furthermore, the biological activity of CHM-04 was comparable to the standard EGFR inhibitor, AG1478 in increasing apoptosis and decreasing the migratory potential of triple-negative breast cancer cells as well as significantly lowering the mammosphere forming ability of breast cancer stem cells. Conclusion: The present study suggests CHM-04, an EGFR inhibitor possessing drug-like properties as a plausible therapeutic candidate against breast cancer.